From within the body: proprioceptive art experiences in the museum. Issue 1 (2nd January 2022) - Dekeyzer, Brigitte
Abstract: This article introduces a new method for understanding the principlesof art and design. It combines meditation techniques, practised and conceptualized proprioceptive body experiences. Starting with a reflection on the so-called 'sensorial turn' and on proprioception in particular, the text offers a protocol for proprioceptive art experiences in the museum and a reflection on its theoretical foundations. The greatest advantages of the method are its inclusive nature, applicability to a broad range of artworks and art forms and its ability to overcome the mind-body dichotomy. It can be done by anyone, regardless of age or physical impairments. The approach achieves the best results in a group led by a museum guide, but individual visitors and families can use it as well, with the proper support from the museum.